RESTORATION OF THE ANATOMICAL SHAPE OF TEETH IN CARIOUS LESIONS: MODERN SOLUTIONS (World Bulletin of Public Health, 2026)
The precise morphological reconstruction of dental tissues following carious degradation is a fundamental prerequisite for maintaining biomechanical equilibrium within the stomatognathic system. This empirical clinical investigation evaluates the morphological retention and marginal integrity of modern restorative interventions, specifically comparing incrementally layered nanohybrid composites against sonic-activated bulk-fill resin systems in complex posterior cavities. Utilizing a split-mouth, randomized clinical design, the study monitored 170 Class II (mesio-occluso-distal) restorations across 85 adult patients over a 12-month functional period. Clinical evaluations were conducted using modified United States Public Health Service (USPHS) criteria, alongside digital volumetric wear analysis. Quantitative diagnostics revealed a pronounced biomechanical advantage for the incremental nanohybrid technique. At the 12-month recall, incrementally layered restorations demonstrated a 94.1% anatomical form retention rate, compared to a rapidly degrading 82.3% within the bulk-fill cohort. Multivariate analysis indicated that managing the cavity configuration factor (C-factor) through stratified application radically minimizes polymerization shrinkage stress, thereby preventing microscopic marginal gap formation. The data dictates a mandatory adherence to biomimetic stratification protocols in advanced restorative dentistry, prioritizing long-term structural integrity and occlusal stability over operational speed
Keywords: Restorative Dentistry; Carious Lesions; Anatomical Reconstruction